KEPEMIMPINAN KRISTEN UNTUK KEADILAN YANG MEMBEBASKAN - Lourine S Joseph (TANGKOLEH PUTAI, 2019)
To be treated fairly and rightly, which is humane and humanist, is everyone's dream, including students at school. This statement is not an empty issue that has no meaning, but empirical facts that occur in every reality of human life, including students in their educational environment. The first person responsible for the dehumanistic reality of injustice for students in schools is the leader, whether the teacher in the class, or the principal as the leader where he studies. One leadership pattern that can be used is Christian leadership that is just and liberating. To study and analyze, the method used is qualitative with a descriptive approach. The result obtained is that liberation from a sense of injustice for a student can be overcome by the leadership of a Christian leader who has an exemplary spirit to serve and help students from helplessness and weakness and freeing them. students to get back their lost human rights, namely the right to be treated fairly and properly at the school where they study.